Profil of Social Interaction of Students at Adabiah 2 Padang High School - Rahmi, Rahmi; Netrawati, Netrawati (Current Issues in Counseling, 2023)
Social interaction is a dynamic relationship concerning the relationship between individuals, individuals with groups, and groups with groups. Good interaction can create a harmonious and warm relationship. However, the phenomena found in the field are students chatting with their friends when the teacher explains the material, students answering questions from the teacher in an angry or displeased tone of voice when advised by the teacher, students use impolite sentences when talking to their friends, students sometimes shout out to friends or when talking, during recess only some students gather and interact with their friends and are busy with their activities. This study uses a quantitative descriptive method. The study population consisted of 414 students and the research sample consisted of 204 students of class X and class XI SMA Adabiah 2 Padang who were selected using a proportional stratified random sampling technique. The research instrument used a Likert scale model questionnaire. Data is processed using descriptive statistical techniques. The overall research results are in the high category with a percentage of 71%.